2016
DOI: 10.17795/jjnpp-25682
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Spironolactone Effects on the Prevention of Progression of Proteinuria in Chronic Kidney Diseases

Abstract: Background: Chronic kidney disease is a persistent disorder in kidney function. This is a progressive disorder characterized by arterial hypertension, glomerular hypertension, proteinuria and some other signs; controlling any of them can reduce the progression of chronic kidney disease. In chronic kidney disease, proteinuria is used as a measure for monitoring nephron injuries and its response to treatment. Angiotensin converting enzyme inhibitors and Angiotensin receptor blockers can reduce the progression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Also in ESRD patients, Takahashi et al reported that their 5 cases of diarrhoea (7.7%) occurred at dose of NAM >1500 mg/d. Shahbazian et al's study reported four patients (16.7%) with diarrhoea that occurred when their dose of NAM increased from 500 to 1000 mg/d. Their symptoms resolved with the reduction in NAM, as did Cheng et al's one patient with diarrhoea, suggesting a possible dose‐dependent relationship.…”
Section: Safety Profilementioning
confidence: 98%
See 4 more Smart Citations
“…Also in ESRD patients, Takahashi et al reported that their 5 cases of diarrhoea (7.7%) occurred at dose of NAM >1500 mg/d. Shahbazian et al's study reported four patients (16.7%) with diarrhoea that occurred when their dose of NAM increased from 500 to 1000 mg/d. Their symptoms resolved with the reduction in NAM, as did Cheng et al's one patient with diarrhoea, suggesting a possible dose‐dependent relationship.…”
Section: Safety Profilementioning
confidence: 98%
“…A number of recent studies have investigated NAM's action in reducing phosphate levels in patients with end‐stage renal disease (ESRD) requiring dialysis …”
Section: Safety Profilementioning
confidence: 99%
See 3 more Smart Citations